1990
DOI: 10.1002/jbm.820240802
|View full text |Cite
|
Sign up to set email alerts
|

Release and detection of dental corrosion products in vivo: Development of an experimental model in rabbits

Abstract: An experimental animal model was developed to investigate the release of metal ions from nonprecious dental alloys. Cast specimens of five Ni-Cr-alloys and Co-Cr-alloys were implanted intramuscularly in rabbits for periods of 2, 4, 8, and 12 weeks. The concentrations of nickel, chromium, cobalt, and molybdenum in the implant-loaded muscles were determined by electrothermal atomic absorption spectrometry (AAS) and neutron activation analysis (NAA). Reference muscle samples of each animal were analyzed to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…The mechanical movement of the implant at every contraction of the muscle will further stimulate the process. A previous report corresponds well with our results showing that intramuscular metal implants liberate metal ions to the surrounding tissue [42].…”
Section: Discussionsupporting
confidence: 93%
“…The mechanical movement of the implant at every contraction of the muscle will further stimulate the process. A previous report corresponds well with our results showing that intramuscular metal implants liberate metal ions to the surrounding tissue [42].…”
Section: Discussionsupporting
confidence: 93%
“…After 5 months, local concentrations of Ni in the soft tissue capsules ranged from 53 to 120 g/mL (900-2100 mol/L), which is equal to or above the 850 mol/L necessary to cause ICAM-1 expression seen in the current study. Other studies have shown lower levels of Ni around such implants, 19 and these discrepancies are not well understood, except that the pH, 13,18 type of alloy, [13][14][15] and tissue 19 all play a role. The observation in the current study that toxic con- shows that basal levels of ICAM-1 were not detectable with medium alone (Med).…”
Section: Discussionmentioning
confidence: 97%
“…1 The corrosion of Ni-based dental alloys has been well documented in vitro [12][13][14] and in vivo, [15][16][17] particularly if the pH of the corroding solution falls below 6.0, 18 a common condition in the mouth. Implanted Ni-based alloys have been shown to elevate Ni levels locally 15,19 and systemically, 20,21 and cellular damage and an inflammatory response have been noted around these implants. 17,22 The biological liabilities of Ni which is released from dental alloys remain undefined.…”
Section: Introductionmentioning
confidence: 98%
“…Over a period of 17 months all patients (n = 327) scheduled for total hip replacement (THR) were subjected to the exclusion criteria of other metallic implants, dental prostheses with cobalt alloys 24,25 and rheumatoid or osteoarthritis of other major joints. Of the 327 patients, 62 with unilateral osteoarthritis or necrosis of the femoral head satisfied these criteria and consented to be included in the study.…”
Section: Methodsmentioning
confidence: 99%